(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Ziziphus abyssinica belongs to the family Rhamnaceae and is traditionally used in the treatment of pneumonia, tonsillitis, Newcastle disease, snake bite, burns, wounds, tachycardia, pectoral pain, migraines and as pain-killers. The objective of this study is to evaluate the phytochemical, physicochemical analysis and safety margin of Z. abyssinica leaf with the hope of assisting in its standardization for quality, purity and safety. The powdered sample of the leaves was extracted with aqueous and methanol and evaluated for physicochemical parameters of the plant. The extracts were subjected to qualitative and quantitative phytochemical analysis and acute toxicity study. Phytochemical screening revealed the presences of alkaloids, flavonoids, saponins, phenols, tannins, glycosides, carbohydrates, anthraquinones and triterpenes in both aqueous and methanol extract. However, steroids were absent; the quantitative phytochemical analysis revealed that flavonoids (134.0 mg/g) were the highest phytochemicals detected in the leaf while the lowest were saponins (6.0 mg/g). The physicochemical parameters evaluated include: moisture content (7.70%), total ash (10.10%), acid insoluble (2.10%), water soluble (7.34%), water extractive value (16.33%) and ethanol extractive value (13.0%). LD50 of both extracts was above 5000 mg/kg and did not cause mortality in all the tested rats. The results of this finding may be useful in laying down standards and for the compilation of a suitable monograph of Z. abyssinica